Up-gradation of Infrastructure at NINMAS to Combat the COVID 19 Pandemic: Preparation during 2020 - Begum, Fatima; Jabin, Zeenat; Ferdousi Begum, Shamim Momtaz (Bangladesh Journal of Nuclear Medicine, 2022)
Abstract not available Bangladesh J. Nuclear Med. 23(1&2): 46-50, 2020